Neuregulin 3 is associated with attention deficits in schizophrenia and bipolar disorder - Meier, Sandra Melanie; Rietschel, Marcella; Wüst, Stefan (The international journal of neuropsychopharmacology, 2013)
Abstract. Linkage and fine mapping studies have established that the neuregulin 3 gene (NRG3) is a susceptibility locus for schizophrenia. Association studies